ISLAMIC EDUCATION FROM A WOMEN'S PERSPECTIVE: AN ANALYSIS OF DR. LIES MARCOES-NATSIR’S THOUGHT IN THE CONTEXT OF GENDER AND INCLUSIVITY - Slamet Pamuji; Moh. Roqib (International Journal of Teaching and Learning, 2025)
Islamic education plays a vital role in shaping the consciousness structure of Muslim societies, including in the aspects of justice and gender equality. However, in practice, the Islamic education system is often still biased against women due to the dominance of patriarchal religious interpretations. This article aims to analyze the thoughts of Dr. Lies Marcoes-Natsir, an Indonesian Muslim anthropologist and feminist, in addressing issues of gender injustice in Islamic education. This research uses a qualitative approach with a library research method, examining Lies Marcoes’s main works and supporting literature related to Islamic feminism, feminist hermeneutics, and inclusive education. The study’s findings show that Lies Marcoes proposes three main strategies in Islamic education: (1) critique of the patriarchal education system that legitimizes the subordination of women; (2) the concept of transformative education that integrates social justice values into the learning process; and (3) the use of feminist hermeneutics as an epistemological approach to re-read religious texts contextually and justly. In addition, she developed an inclusivity strategy that covers structural, cultural, and pedagogical aspects, and emphasized the importance of women's representation in the leadership of Islamic educational institutions. Marcoes’s thoughts contribute significantly to formulating an Islamic education that is not only normatively religious but also substantively inclusive and just. This article is expected to serve as a reference for policymakers, educators, and education activists in building a transformative Islamic education system that is responsive to gender justice